Preliminary Evaluation of the Transdiagnostic Educational Package based on the Schema Therapy, Self-Compassion and Emotion Regulation Model in Cardiac Health-Related Behaviors - Ahmad Amiri Pijakelai; Mehdi Akbari; Shahram MohammadKhani; Jafar Hasani (روانشناسی بالینی و شخصیت, 2023)
Introduction: Few studies have examined integrative models in the context of chronic diseases including cardiovascular disease. In this context, the aim of the present study was the preliminary evaluation of the transdiagnostic educational package based on the schema therapy model, self-compassion model, and emotion regulation model in cardiac health-related behaviors. Method: 3 people were selected in a single-case pilot study and received an intervention package based on the research model during 15 sessions. Participants responded to the cardiac health behavior scale (Song et al., 2018), Self-Compassion Questionnaire (Neff, 2003), Young's Early Maladaptive Schemas Questionnaire (YSQ-S3), and Emotion Regulation Scale (Gross and John, 2003). The data were analyzed by visual analysis of graphs analysis, indicators of recovery percentage, reduction percentage, and Cohen's effect size.Results: The findings showed that the recovery percentage of the first, second, and third participants in the reappraisal respectively was 40, 38, and 43 percent, suppression was 46, 46, and 45 percent, self-compassion was 41, 34, and 41 percent and cardiac health-related behaviors were 32, 33 and 35 percent.Results: also, the reduction percentage of the first, second, and third participants in reappraisal respectively was 67, 62, and 76 percent, suppression was 32, 32, and 31 percent, self-compassion was 68, 51, and 69 percent, and cardiac health-related behaviors were 47, 50 and 54 percent.The effect size of the reappraisal for the first, second, and third participants was -0.91, -0.79 and -0.80 respectively, suppression was 0.83, 0.91, and 0.93, self-compassion was -0.78, -0.86 and -0.90 and cardiac health related-behaviors were -0.83, -0.75 and -0.87.Discussion and Conclusion: According to the findings supporting the proposed model, the transdiagnostic educational package based on schema therapy, emotion regulation, and self-compassion model can be used to improve cardiac health-related behaviors.